The temperature monitoring during the reactor core material irradiation by analyzing the structure of graphite-like boron nitride - Ye.I. Isaev; V.A. Stepanov; P.A. Stepanov (Nuclear Energy and Technology, 2016)
Possibility has been shown for determining the temperature of in-core irradiation using a single structural analysis of irradiated boron-nitride ceramics without a time-consuming research stage, including post-irradiation annealing. This is explained by the fact that steady structural states, depending on temperature and not depending on exposure dose, may develop in nanocrystalline graphite-like ceramic boron nitride in high-dose environments. A temperature dependence of the position of the X-ray line (002) has been obtained for the radiation-induced steady structure of ceramics. This dependence can be used for determination of temperature in a fast reactor in a range of 690 to 1870K. It has been found using X-ray structural analysis that reaction-sintered boron-nitride ceramics in the initial and irradiated states comprises two structural components. The first one corresponds to defect-free hexagonal and rhombohedral structures. The X-ray line displacements relate to the second component the nanocrystallites of which contain a great deal of microdeformations stabilized by clusters of vacancy discs.